An exploration on how Information Systems (IS) executives engage in the practice of aligning business and IS strategies in Pubic Service Organisations (PSOs) - Sarhan, Mohammad (Trinity College (Dublin, Ireland). Trinity Business School, 2017)
This thesis is situated in the domain of Strategic Alignment (SA) within the field of Information system (IS) strategy to explore "How do Information System (IS) executives engage in the practice of aligning business and IS strategies in Public Service Organisations (PSOs)?". SA research is experiencing a 'practice turn' from a focus on what SA can do for organisational level performance to a newer focus on what practices constitute SA. Underlying this turn are impulses to move the field beyond current problematic overwhelming evidence on what-to-aligning rather than how-to-aligning, that is, to animate the 'worldliness' of SA enactment as an activity that practitioners do as opposed to the representation of SA under the dichotomy of 'aligned' vs. 'misaligned' organisations. From its inception, by leveraging the theory of practice, the pragmatist conception of what practitioners do is enjoying a renaissance in the Strategy-as-Practice (SAP) perspective within the strategic management field. As such, SAP perspective has been taken in this thesis as an alternative theoretical lens to facilitate inquiring into the micro-end of the spectrum by investigating aligning activities of IS executives within their situated practices.
Keywords: Business, Ph.D.; PhD Trinity College Dublin, 2017